2016
DOI: 10.3389/fimmu.2016.00268
|View full text |Cite
|
Sign up to set email alerts
|

Is the Antitumor Property of Trypanosoma cruzi Infection Mediated by Its Calreticulin?

Abstract: Eight to 10 million people in 21 endemic countries are infected with Trypanosoma cruzi. However, only 30% of those infected develop symptoms of Chagas’ disease, a chronic, neglected tropical disease worldwide. Similar to other pathogens, T. cruzi has evolved to resist the host immune response. Studies, performed 80 years ago in the Soviet Union, proposed that T. cruzi infects tumor cells with similar capacity to that displayed for target tissues such as cardiac, aortic, or digestive. An antagonistic relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 93 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…Later, researchers developed an anticancer experiment in which T. cruzi extracts were directly inoculated in peritumoral areas over different tumors, and all of the results showed a reduction in tumor size [ 4 ]. However, the work was hampered by controversial results and the complicated international political situation, and so the molecular basis of this phenomenon has remained elusive [ 5 ]. Moreover, several live-attenuated protozoan parasites including Leishmania infantum and L. tropica [ 6 ], Neospora caninum [ 7 ], and Toxoplasma gondii [ 8 ] have all lately been employed as antitumor biological agents via intratumoral injection, all of which decreased tumor development and local inflammation ( Figure 1 ).…”
Section: Tumor Therapy With the Injection Of Parasitementioning
confidence: 99%
“…Later, researchers developed an anticancer experiment in which T. cruzi extracts were directly inoculated in peritumoral areas over different tumors, and all of the results showed a reduction in tumor size [ 4 ]. However, the work was hampered by controversial results and the complicated international political situation, and so the molecular basis of this phenomenon has remained elusive [ 5 ]. Moreover, several live-attenuated protozoan parasites including Leishmania infantum and L. tropica [ 6 ], Neospora caninum [ 7 ], and Toxoplasma gondii [ 8 ] have all lately been employed as antitumor biological agents via intratumoral injection, all of which decreased tumor development and local inflammation ( Figure 1 ).…”
Section: Tumor Therapy With the Injection Of Parasitementioning
confidence: 99%
“…was proposed that this infection mediates an adaptive immune response with significant antitumor effects (23).…”
Section: Increasing Cancer-related Inflammationmentioning
confidence: 99%
“…Another step in the research of increasing cancer-related inflammation was made about 80 years ago by Roskin and colleagues by using Trypanosoma cruzi (the protozoan agent of Chagas' disease). It was proposed that this infection mediates an adaptive immune response with significant antitumor effects ( 23 ).…”
Section: Increasing Cancer-related Inflammationmentioning
confidence: 99%
“…It has also been suggested that the translocated calreticulin binds the host complement component C1 and thereby facilitates parasite invasion [ 58 ]. Due to these properties, the T. cruzi calreticulin has also been regarded to possess an inhibitory effect on cancerous cells [ 59 ]. In Leishmania spp., loss of calreticulin affects the parasite secretory pathway and reduces parasite virulence indicating that ER calcium may have an important role in governing virulence of trypanosomatid parasites [ 60 , 61 ].…”
Section: Calcium Transport Proteins In the Membrane Of The Endoplamentioning
confidence: 99%